Composite dielectric structure realized by adopting mixed ceramic material and manufacturing method thereof

By using interlaced layers of mixed ceramic and glass materials to make a composite dielectric structure, the problem of different dielectric constants of dielectric materials of antenna components and filter components is solved, and efficient combination and performance improvement is achieved.

CN119852042APending Publication Date: 2025-04-18CYNTEC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410386107.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-17
Filing Date
2024-04-01
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

When manufacturing millimeter wave antenna modules, the dielectric constants of the dielectric materials required for antenna elements and filter elements are different, resulting in high volume density of the dielectric structure and making it difficult to achieve ideal combinations.

Method used

A composite dielectric structure made of mixed ceramic materials, including ceramic layers with different dielectric constants and interlaced layers of glass materials, is formed through a low-temperature co-firing process to achieve an effective combination of antenna elements and filter elements.

Benefits of technology

The effective combination of different dielectric constant materials is realized, which reduces cracks and defects inside and outside the low-temperature cofired ceramics, and improves the performance of the millimeter wave antenna module.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852042A_ABST
    Figure CN119852042A_ABST
Patent Text Reader

Abstract

A composite dielectric structure includes a first dielectric ceramic layer including a first dielectric ceramic material having a first dielectric constant; the second dielectric ceramic layer comprises a second dielectric ceramic material with a second dielectric constant; the staggered layer comprises a glass material or a glass-based material, and the volume percent of the staggered layer is 93%-100% of the total material of the staggered layer. The interlaced layer is disposed between the first surface of the first dielectric ceramic layer and the second surface of the second dielectric ceramic layer for joining the first dielectric ceramic layer and the second dielectric ceramic layer to form the composite dielectric structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dielectric structure, in particular to a composite dielectric structure realized by using a mixed ceramic material. The present invention also relates to a method for manufacturing the composite dielectric structure realized by using a mixed ceramic material. Background Art

[0002] As the fifth generation of mobile communication technology (5th generation mobile networks or 5th generation wireless systems, hereinafter referred to as 5G) enters people's daily lives, the optimization of the design and manufacture of the millimeter wave antenna modules used in it has also become an important topic. At present, the global unified 5G frequency band mainly falls on all or part of the 26GHz band (24.25GHz-27.5GHz), 40GHz band (37GHz-43.5GHz) and 66GHz-71GHz band. The 26GHz band is a popular band that the global 5G industry strives to use because of its advantages such as low frequency, large bandwidth, and relatively low difficulty in equipment implementation. However, this band is adjacent to the band used by satellite earth exploration services. Therefore, when designing millimeter wave antenna modules, high-frequency filters can be used to filter out signal interference.

[0003] However, the antenna elements and filter elements in the millimeter wave antenna module require different dielectric materials for their manufacture. Usually, low-K dielectric materials are used to make antenna elements, while high-K dielectric materials are used to make filter elements, so that one of the antenna elements or filter elements of the dielectric structure has a high volume density. If materials with the same or similar permittivity are used to produce these two elements, problems such as the high-frequency filter being too large or the high-frequency antenna losing too much energy will arise. Therefore, how to combine materials with different dielectric constants will be the technical key to manufacturing an ideal millimeter wave antenna module. Summary of the invention

[0004] Therefore, the present invention provides a composite dielectric structure comprising ceramic layers with different dielectric constants, which is suitable for producing a high-frequency antenna module with a high-frequency filter.

[0005] The present invention also provides a method for manufacturing a composite dielectric structure, wherein the method performs co-firing in an atmospheric environment without external pressure, and the composite dielectric structure comprises ceramic layers with different dielectric constants.

[0006] In one aspect of the present invention, a composite dielectric structure is provided, the structure comprising a first dielectric ceramic layer comprising a first dielectric ceramic material having a first dielectric constant; a second dielectric ceramic layer comprising a second dielectric ceramic material having a second dielectric constant; and an interleaved layer comprising a glass material or a glass-based material, the volume percentage of which is 93%-100% of the total material of the interleaved layer. The interleaved layer is disposed between a first surface of the first dielectric ceramic layer and a second surface of the second dielectric ceramic layer, and is used to bond the first dielectric ceramic layer and the second dielectric ceramic layer to form the composite dielectric structure.

[0007] According to one embodiment of the present invention, the first dielectric constant is greater than the second dielectric constant.

[0008] According to another embodiment of the present invention, the first dielectric constant is greater than 4 times the second dielectric constant.

[0009] According to another embodiment of the present invention, the glass material or the glass-based material of the cross-layer includes a high-temperature liquid phase material having a softening point lower than the softening point of the first dielectric ceramic material and the softening point of the second dielectric ceramic material.

[0010] According to another embodiment of the present invention, the softening point of the high temperature liquid phase material is 400-600°C.

[0011] According to another embodiment of the present invention, the glass oxide powder is made of a glass material or a glass-based material selected from a group consisting of SiO2, B2O3, GeO2, P2O5 and combinations thereof; a glass composite material (glass complex) selected from a group consisting of SiO2-B2O3-K2O-HfO, SiO2-B2O3 and combinations thereof; a complex of glass and alkali oxide selected from a group consisting of potassium oxide, sodium oxide and combinations thereof; or a mixture of glass comprising phosphate glass and an inorganic oxide selected from a combination of silicon oxide, aluminum oxide, potassium oxide, sodium oxide and / or boron oxide.

[0012] According to another embodiment of the present invention, the interleaved layer further comprises a ceramic material, the volume percentage of which is 0%-7% of the total material of the interleaved layer.

[0013] According to another embodiment of the present invention, a third thickness of the interleaved layer ranges from 30 μm to 70 μm, and is smaller than a first thickness of the first dielectric ceramic layer and a second thickness of the second dielectric ceramic layer.

[0014] According to another embodiment of the present invention, the softening point of the glass material or the glass-based material ranges from 500°C to 600°C and is at least 100°C lower than the softening point of the ceramic powders of the first dielectric ceramic layer and the second dielectric ceramic layer, respectively, and the thickness of the interleaved layer ranges from 40 micrometers (μm) to 50 micrometers (μm).

[0015] According to another embodiment of the present invention, the first dielectric ceramic material and / or the second dielectric ceramic material comprises a mixture of the glass material or the glass-based material and ceramic powder; the volume percentage of the glass material or the glass-based material in the interleaved layer is higher than the volume percentage of the glass material or the glass-based material in the mixture of the first dielectric ceramic material, and higher than the volume percentage of the glass material or the glass-based material in the mixture of the second dielectric ceramic material.

[0016] According to another embodiment of the present invention, the volume percentage of the glass material or the glass-based material in the first dielectric ceramic layer is 13%-33%, and the volume percentage of the glass material or the glass-based material in the second dielectric ceramic layer is 53%-63%.

[0017] According to another embodiment of the present invention, in the mixture of the first dielectric ceramic material and / or the second dielectric ceramic material, the glass material or the glass-based material is formed on at least a portion of the surface of the ceramic powder; the ceramic powders of the first dielectric ceramic material and the second dielectric ceramic material are different; and the staggered layer is in direct contact with the first dielectric ceramic layer and the second dielectric ceramic layer.

[0018] According to another embodiment of the present invention, the first dielectric ceramic layer is disposed in a filter element, and the second dielectric ceramic layer is disposed in an antenna element.

[0019] According to another embodiment of the present invention, the first dielectric ceramic layer and the second dielectric ceramic layer are stacked with the staggered layer along a stacking direction, and a thickness of the first dielectric ceramic layer is different from a thickness of the second dielectric ceramic layer in the stacking direction.

[0020] Another aspect of the present invention is a method for manufacturing a composite dielectric structure using a mixed ceramic material, the method comprising the following steps: providing a green embryo of at least one first dielectric ceramic layer, wherein the green embryo comprises a first dielectric ceramic material and has a first dielectric constant; providing a green embryo of at least one second dielectric ceramic layer, wherein the green embryo comprises a second dielectric ceramic material and has a second dielectric constant; providing at least one green embryo of an interleaved layer; stacking the green embryo of the interleaved layer between the green embryo of the first dielectric ceramic layer and the green embryo of the second dielectric ceramic layer to form a multilayer structure, wherein the interleaved layer comprises a glass material or a glass-based material powder, the weight percentage of which is at least 90%-100% of the total material of the green embryo of the interleaved layer; and performing a low temperature co-firing process on the multilayer structure to form a composite dielectric structure.

[0021] According to one embodiment of the present invention, the green body of at least the first or second dielectric ceramic layer is mixed with ceramic powder, solvent and binder, wherein the third thickness of the staggered layer is less than a first thickness of the first dielectric ceramic layer and less than a second thickness of the second dielectric ceramic layer.

[0022] According to another embodiment of the present invention, the first dielectric constant is greater than the second dielectric constant.

[0023] According to another embodiment of the present invention, the first dielectric constant is greater than four times the second dielectric constant.

[0024] According to another embodiment of the present invention, the interleaved layer comprises a high temperature liquid phase material having a softening point lower than the softening point of the first dielectric ceramic material and the softening point of the second dielectric ceramic material.

[0025] According to another embodiment of the present invention, the softening point of the high temperature liquid phase material is 400-600°C.

[0026] According to another embodiment of the present invention, the glass material or the glass-based material powder is selected from the group consisting of alkali oxides, inorganic glass mixtures and combinations thereof.

[0027] According to another embodiment of the present invention, the inorganic glass mixture comprises a mixture of phosphate glass, silicon oxide, aluminum oxide, potassium oxide, sodium oxide and boron oxide; the thickness of at least the green body of the interleaved layer is between 40 micrometers (μm) and 50 micrometers (μm); the softening point of the glass material or the glass-based material powder of at least the green body of the interleaved layer is between 500° C. and 600° C., and is at least 100° C. lower than the softening point of each of the first dielectric ceramic layer and the second dielectric ceramic layer.

[0028] According to another embodiment of the present invention, at least the material of the interlaced layers of green body further comprises a binder and a solvent, and the weight percentages of the glass material or the glass-based material powder, the binder and the solvent are 40-60%, 6-15% and 40-60% respectively.

[0029] According to another embodiment of the present invention, the first dielectric ceramic material and / or the second dielectric ceramic material comprises a mixture of glass material or glass-based material powder and ceramic powder; the weight percentage of the glass material or glass-based material powder in the interlaced layer green body is higher than the weight percentage of the glass material or glass-based material powder in the first dielectric ceramic material mixture, and higher than the weight percentage of the glass material or glass-based material powder in the second dielectric ceramic material mixture.

[0030] According to another embodiment of the present invention, the material of at least one embryo in the staggered layer contains 93%-100% by volume of glass material or glass-based material powder and 5%-7% by volume of ceramic powder; the first dielectric ceramic material and / or the second dielectric ceramic material contains a mixture of glass material or glass-based material powder and ceramic powder; the weight percentage of the glass material or glass-based material powder in the material of at least the embryo in the staggered layer is 90%-100%; the weight percentage of the glass material or glass-based material powder in the material of at least one embryo of the first dielectric ceramic layer is 10%-30%; the weight percentage of the glass material or glass-based material powder in at least the embryo of the second dielectric ceramic is 50%-60%.

[0031] According to another embodiment of the present invention, at least one embryonic form of the first dielectric ceramic layer and at least one embryonic form of the second dielectric ceramic layer are stacked with at least one embryonic form of the interleaved layer along a stacking direction, and a first thickness of the embryonic form of the first dielectric ceramic layer and a second thickness of the embryonic form of the second dielectric ceramic layer are different in the stacking direction.

[0032] The present invention can achieve ideal co-firing matching and reactivity by adding a material capable of absorbing stress generated when different heterogeneous ceramics are co-fired, thereby reducing cracks and defects inside and outside the low temperature co-fired ceramic (LTCC). BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above content of the invention will become more easily understood by those skilled in the art after reading the following detailed description and accompanying drawings, in which:

[0034] Figure 1Ais a schematic diagram showing a composite ceramic structure according to an embodiment of the present invention;

[0035] Figure 1B It indicates Figure 1A Schematic diagram of an example of a composite ceramic structure;

[0036] Figure 1C It indicates Figure 1A A schematic diagram of another example of a composite ceramic structure;

[0037] Figure 1D It indicates Figure 1A A schematic diagram of a further example of a composite ceramic structure;

[0038] Figure 1E It indicates Figure 1A A schematic diagram of another example of a composite ceramic structure;

[0039] Figure 2 is a cross-sectional view showing a dielectric ceramic material of a first dielectric ceramic layer, a second dielectric ceramic layer or an interleaved layer after a co-firing process according to an embodiment of the present invention;

[0040] Figure 3A is a schematic diagram showing a tape casting coating machine suitable for manufacturing a composite dielectric structure of a staggered layer, a first dielectric ceramic material layer and a second dielectric ceramic material layer according to an embodiment of the present invention;

[0041] Figure 3B It indicates that Figure 3A A schematic diagram of a cutting process of a green sheet used to form an interleaved layer, a first dielectric ceramic material layer or a second dielectric ceramic material layer in the process shown;

[0042] Figure 3C is a schematic diagram showing a stacking process of forming a composite dielectric structure by forming a staggered layer, a first dielectric ceramic layer and a second dielectric ceramic layer; and

[0043] Figure 3D It means that through Figure 3B After introducing a conductive hole (via) pattern or a conductive pattern into the first dielectric ceramic material layer or the second dielectric ceramic material layer, a conductive hole (via) pattern or a conductive pattern is formed. Figure 3C Schematic diagram of the structure of the first dielectric ceramic layer and the second dielectric ceramic layer.

[0044]

Explanation of symbols

[0045] 11: First dielectric ceramic layer

[0046] 12: Second dielectric ceramic layer

[0047] 13: Staggered Layers

[0048] d1: first thickness

[0049] d2: second thickness

[0050] d3: third thickness

[0051] 20: Glass

[0052] 21: Ceramic powder

[0053] 22: Void

[0054] 30: Casting coating machine material

[0055] 301: Preparation of thin strips

[0056] 31, 32: Dielectric ceramic layer

[0057] 33: Staggered Layers

[0058] 4: Composite dielectric structure

[0059] 401: Conductive hole pattern

[0060] 402: Conductive pattern

[0061] 403, 404: Electrode

[0062] 41: Filter circuit

[0063] 42: Antenna circuit layout

[0064] 400: Millimeter wave antenna module DETAILED DESCRIPTION

[0065] The present invention will now be described in more detail with the following examples. It should be noted that the following description of preferred embodiments of the present invention is only for the purpose of illustration and description. It is not intended to be exhaustive or limited to the precise form disclosed.

[0066] See also Figure 1A, which is a schematic diagram of a composite ceramic structure developed by the present invention to improve the existing means, the composite ceramic structure includes a first dielectric ceramic layer 11 made of a first dielectric ceramic material, a second dielectric ceramic layer 12 made of a second dielectric ceramic material, and an interleaving layer 13. The first dielectric ceramic layer 11 has a first dielectric constant (permittivity, or dielectric constant) Dk1 greater than the second dielectric constant Dk2 of the second dielectric ceramic layer 12. The interleaving layer 13 includes a glass-based material, such as glass or a glass complex. The glass-based material accounts for 90 to 100 wt% of the weight of the overall material forming the interleaving layer 13. The interleaving layer 13 is disposed between the first surface of the first dielectric ceramic layer 11 and the second surface of the second dielectric ceramic layer 12, and the first dielectric ceramic layer 11 is combined with the second dielectric ceramic layer 12 to form a composite ceramic structure. In this embodiment, the interleaving layer 13 is combined with the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12 in direct contact to form a composite ceramic structure.

[0067] In this embodiment, the first dielectric ceramic layer 11 is a high-K dielectric material, and its first dielectric constant Dk1 is greater than 20 (Dk1>20), for example, 20.523. In contrast, the second dielectric ceramic layer 12 is a low-K dielectric material, and its second dielectric constant Dk2 is less than 5 (Dk2<5), for example, 3.9, so that the composite ceramic structure has a high volume density. In this embodiment, the first ceramic material of the first dielectric ceramic layer 11 and the second ceramic material of the second dielectric ceramic layer 12 are different. When the first dielectric ceramic layer 11 is used as the insulating part of the filter element, it also includes a conductive structure and can be a multi-layer structure, and the second dielectric ceramic layer 12 is used as the insulating part of the antenna element, which also includes a conductive structure and can also be a multi-layer structure. The first dielectric constant Dk1 is preferably greater than the second dielectric constant Dk2, and more preferably, Dk1 / Dk2 is greater than 4. In this case, a millimeter wave antenna module can be produced, including a filter element and an antenna element, so as to be suitable for the required frequency band without being interfered by the signal. The conductive structure included in the filter element and the antenna element may include at least one conductive pattern and at least one conductive via disposed in the insulating portion. In this embodiment, the interleaved layer 13 is formed by a low-temperature cofiring process at substantially one atmosphere to combine the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12 together, so that the filter element and the antenna element can be electrically connected through the conductive via (not shown) disposed in the interleaved layer 13.

[0068] For example, the interleaved layer 13 may be formed of a high-temperature liquid-phase material that is in a liquid phase rather than a gas phase at a co-firing temperature greater than 100° C., and has a softening point lower than the softening points of the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12. Therefore, in a low-temperature cofiring process, the interleaved layer 13 may absorb various stresses, such as shrinkage stress and expansion stress generated during heating and cooling. The softening point of the interleaved layer 13 may be, for example, 400-600° C., and preferably between 500-600° C., which is at least 100° C. lower than the softening point of the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12. The first dielectric ceramic layer 11, the interleaved layer 13, and the second dielectric ceramic layer 12 as described above may be combined together by a low-temperature cofiring process at substantially one atmosphere to form a desired composite ceramic structure. In an embodiment, the softening point of the glass-based material of the interleaved layer 13 may be, for example, 400-600° C., and preferably between 500-600° C., which is at least 100° C. lower than the softening point of the ceramic powder of the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12. Since the softening points of the glass-based materials of the interleaved layer 13, the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12 are all higher than the soldering temperature, which is generally 270° C., when the electronic component is soldered to a system printed circuit board (system PCB), the interleaved layer 13, the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12 will not be adversely affected by softening during the soldering process.

[0069] In an embodiment, the interleaved layer 13 comprises a material formed from glass oxide powders. Prior to the cofiring process, the glass oxide powders are combined with an adhesive and a solvent to form a green body of the interleaved layer 13. It should be noted that after the cofiring process, the glass oxide powders are softened and fused with the softened ceramic powder, such that the resulting interleaved layer 13 contains ceramic material in a volume percentage of about 0% to 7% of the interleaved layer. The above-mentioned glass oxide powders may be selected from a group consisting of glass materials or glass-based materials composed of SiO2, B2O3, GeO2, P2O5, and combinations thereof; a glass complex selected from a group consisting of SiO2-B2O3-K2O-HfO, SiO2-B2O3, and combinations thereof; a complex of glass and alkali oxide selected from a group consisting of potassium oxide, sodium oxide, and combinations thereof; or made from a mixture of a glass containing phosphate glass and an inorganic oxide selected from a combination of silicon oxide, aluminum oxide, potassium oxide, sodium oxide, and / or boron oxide. Preferably, the content of the glass material or glass-based material in the interleaved layer 13 is higher than the content of the glass material or glass-based material in the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12. In one embodiment, the volume percentage of the glass material or glass-based material in the second dielectric ceramic layer 12 is higher than the volume percentage of the glass material or glass-based material in the first dielectric ceramic layer 11. For example, after the cofiring process, the volume percentage of the glass material or glass-based material in the interleaved layer 13 accounts for 93% - 100% of the overall material; the volume percentage of the glass material or glass-based material in the first dielectric ceramic layer 11 accounts for 13% - 33% of the overall material; the volume percentage of the glass material or glass-based material in the second dielectric ceramic layer 12 accounts for 53% - 63% of the overall material. The third thickness d3 of the interleaved layer 13 is between 30 - 70 micrometers (μm), and preferably 40 - 50 micrometers (μm), and is less than the first thickness d1 of the first dielectric ceramic layer 11 and the second thickness d2 of the second dielectric ceramic layer 12 (d3 < d1, d3 < d2). The low-temperature cofiring process is carried out at 875 °C under one atmosphere for 2 hours. The cofiring temperature is higher than the softening point of the glass oxide powders of the interleaved layer 13 and lower than the softening points of the dielectric ceramic material powders of the first dielectric ceramic layer 11, the second dielectric ceramic layer 12, and the interleaved layer 13. Then, the stacked structure described above can be integrated into a composite ceramic structure with desired properties.Before the co-firing process, it is preferred that the weight percentage of the glass material or glass-based material powder (for green sheet) in the overall material of the cross-layer 13 is 90%-100% of the overall material; the weight percentage of the glass material or glass-based material powder (for green sheet) in the overall material of the first dielectric ceramic layer 11 is 10%-30% of the overall material; and the weight percentage of the glass material or glass-based material powder (for green sheet) in the overall material of the second dielectric ceramic layer 12 is 50%-60% of the overall material.

[0070] Please refer to Figure 1B-1E , which schematically shows an example of a first thickness d1 of the first dielectric ceramic layer 11, a second thickness d2 of the second dielectric ceramic layer 12, and a third thickness d3 of the interleaved layer 13. In one embodiment, the thicknesses d1, d2, d3 of the first dielectric ceramic layer 11, the second dielectric ceramic layer 12, and the interleaved layer 13 can be adjusted by stacking a selected number of dielectric layers of equal thickness (d1=d2). Even though the thickness d1 of the first dielectric ceramic layer 11 and the thickness d2 of the second dielectric ceramic layer 12 may be different (d1≠d2), due to the presence of the interleaved layer 13, the stress generated in the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12 having different thicknesses can still be effectively absorbed. In other words, the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12 can be combined together to form a composite ceramic structure for a millimeter wave antenna module.

[0071] In the co-fired structure of the interleaved layer 13, the first dielectric ceramic layer 11 and the second dielectric ceramic layer 12, all the glass oxide powders are melted together, thereby eliminating grain boundaries. When the third thickness d3 of the interleaved layer 13 is in a preferred range, such as 30 microns (μm)-70 microns (μm), it can have the effect of improving bonding strength and absorbing stress. In this case, the first thickness d1 of the first dielectric ceramic layer 11 and the second thickness d2 of the second dielectric ceramic layer 12 can be flexibly designed and do not have to be similar to each other. The weight percentages of glass oxide powder, adhesive and solvent are 40-60%, 6-15% and 40-60% respectively. Subsequently, in the co-firing process, the adhesive and solvent are burned or evaporated and no longer exist in the composite dielectric structure.

[0072] Since the first dielectric ceramic layer 11 has a relatively high dielectric constant and the second dielectric ceramic layer 12 has a relatively low dielectric constant, the first dielectric ceramic layer 11 is suitable for filter elements, and the second dielectric ceramic layer 12 is suitable for antenna elements. The operating frequency band (frequency region) of the filter element and the antenna element can be located in the 26 GHz region (24.25 GHz-27.5 GHz), the 40 GHz region (37 GHz-43.5 GHz) or the 66 GHz-71 GHz region. In this way, the composite dielectric structure manufactured according to the present invention can successfully integrate materials with different dielectric constants, and realize the application of antenna elements and filter elements in the same millimeter wave antenna module.

[0073] Please refer to Figure 2 , which shows a first dielectric ceramic layer, a second dielectric ceramic layer or an interleaved layer of dielectric ceramic materials that have undergone a co-firing process according to an embodiment of the present invention. The first dielectric ceramic material and the second dielectric ceramic material may include, for example, glass and ceramic powder. The ceramic powder in the mixture of the first dielectric ceramic material and / or the second dielectric ceramic material may include ZrO2 or ZnO. As shown in the figure, in the mixture of the first dielectric ceramic material and / or the second dielectric ceramic material, glass 20 is formed on at least a portion of the surface of the ceramic powder 21, and there are some voids 22. In one embodiment, the ceramic powders 21 of the first dielectric ceramic material and the second dielectric ceramic material are different. In other words, the ceramic powder 21 combined with the glass 20 can reduce the stress on the ceramic powder 21. Examples of glass / ceramic powder mixtures include but are not limited to SiO2-B2O3-K2O-HfO / ZrO2, SiO2-B2O3-K2O-HfO / ZrO2-Li 1+x -yNb 1-x-3y Ti x+4y O3, SiO2-B2O / ZnO-Nb2O5-TiO2, etc.

[0074] Figure 3A , 3B 3C respectively illustrate, in schematic form, a method for making a composite dielectric structure according to an embodiment of the present invention. First, raw material powder (e.g., ceramic powder and / or glass material or glass-based material powder) is added to a solvent with a dispersant, and then selectively ground and dispersed into a powder slurry. Next, the dispersed slurry is added to a plasticizer and an adhesive that are pre-dissolved in a solvent. The mixture is continuously stirred until the components are evenly dispersed. Thus, the preparation of a green slurry that meets a preset viscosity range is completed. Subsequently, as Figure 3AAs shown, a green slurry is poured onto a pre-prepared thin strip 301 using a tape-casting coater 30. The blade gap parameter of the tape-casting coater 30 is adjusted to obtain green-ware sheets of the interleaved layers, the first dielectric ceramic material layer, and the second dielectric ceramic material layer, each having a thickness within a preset thickness range. By selectively using raw materials of different compositions, the properties of the interleaved layers and the dielectric ceramic material layers produced can be adjusted.

[0075] Further references Figure 3B The interleaved layers or dielectric ceramic material layers on the prepared thin strip 301, i.e., the green sheet, are cut into appropriate sizes. Conductive hole patterns 401 and conductive patterns 402 (see FIG. 4 ) are formed in the first and second dielectric ceramic material layers, respectively. Figure 3D ) to form dielectric ceramic layers 31 and 32. The dielectric ceramic layers 31 and 32 are stacked on opposite sides of the staggered layer 33 to form a multilayer structure of a composite dielectric structure of an electronic component, module or substrate, such as Figure 3C As shown. According to different stacking configurations, various components with different thicknesses and / or different layouts can be obtained. In this embodiment, the dielectric constant of the first dielectric ceramic layer 31 is greater than the dielectric constant of the second dielectric ceramic layer 32, and the softening point of the staggered layer 33 is lower than the softening points of the first and second dielectric ceramic layers 31 and 32. The electronic component also includes a pair of electrodes 403 and 404 ( Figure 3D ), through this pair of electrodes, the electronic components can be soldered to the system printed circuit board (system PCB) and electrical connection can be achieved.

[0076] See also Figure 3D .based on Figure 3C The multilayer structure shown can generate a composite dielectric structure 4 integrating multiple filter circuits 41 and multiple antenna circuit layouts 42 after a co-firing process. Then, the composite dielectric structure 4 is cut into independent millimeter wave antenna modules 400.

[0077] As described above, materials with different dielectric constants can be combined by adding a material that can absorb the stress generated during the co-firing process between different heterogeneous ceramics. In addition, a dielectric ceramic material with a high dielectric constant and a dielectric ceramic material with a low dielectric constant can be co-fired in an atmospheric environment without the need for external pressure. Therefore, an ideal co-firing match and reactivity can be obtained, thereby reducing cracks and defects inside and outside the ceramic body (LTCC) during the low temperature co-firing process.

[0078] Although the present invention has been described according to what is currently considered to be the most practical and preferred embodiments, it should be understood that the present invention is not necessarily limited to the disclosed embodiments. On the contrary, it is intended to cover various modifications and similar arrangements contained within the spirit and scope of the appended claims, which are consistent with the broadest interpretation, thereby covering all such modifications and similar structures.

Claims

1. A composite dielectric structure comprising: a first dielectric ceramic layer comprising a first dielectric ceramic material having a first dielectric constant; a second dielectric ceramic layer comprising a second dielectric ceramic material having a second dielectric constant; and A staggered layer includes a glass material or a glass-based material, the volume percentage of which is 93%-100% of the total material of the staggered layer, the staggered layer is arranged between a first surface of the first dielectric ceramic layer and a second surface of the second dielectric ceramic layer, and the first dielectric ceramic layer and the second dielectric ceramic layer are bonded to form the composite dielectric structure. 2 . The composite dielectric structure of claim 1 , wherein the first dielectric constant is greater than the second dielectric constant. 3 . The composite dielectric structure of claim 2 , wherein the first dielectric constant is greater than 4 times the second dielectric constant.

4. The composite dielectric structure of claim 1, wherein the glass material or the glass-based material of the cross-layer comprises a high temperature liquid phase material having a softening point lower than the softening point of the first dielectric ceramic material and the softening point of the second dielectric ceramic material. 5 . The composite dielectric structure as claimed in claim 4 , wherein the high temperature liquid phase material has a softening point of 400-600° C.

6. The composite dielectric structure of claim 1 , wherein the glass oxide powder is made of a glass material or glass-based material selected from the group consisting of SiO 2 , B 2 O 3 , GeO 2 , P 2 O 5 and combinations thereof; a glass composite material selected from the group consisting of SiO 2 —B 2 O 3 —K 2 O —HfO, SiO 2 —B 2 O 3 and combinations thereof; a composite of glass selected from the group consisting of potassium oxide, sodium oxide and combinations thereof and alkali metal oxides; or a mixture of glass including phosphate glass and an inorganic oxide selected from the group consisting of silicon oxide, aluminum oxide, potassium oxide, sodium oxide and / or boron oxide. 7 . The composite dielectric structure of claim 1 , wherein the staggered layer further comprises a ceramic material, the volume percentage of which is 0%-7% of the total material of the staggered layer. 8 . The composite dielectric structure of claim 1 , wherein a third thickness of the staggered layer ranges from 30 μm to 70 μm and is smaller than a first thickness of the first dielectric ceramic layer and a second thickness of the second dielectric ceramic layer.

9. The composite dielectric structure of claim 1 , wherein the softening point of the glass material or the glass-based material ranges from 500° C. to 600° C. and is at least 100° C. lower than the softening point of the ceramic powders of the first dielectric ceramic layer and the second dielectric ceramic layer, respectively, and the thickness of the interleaved layer ranges from 40 μm to 50 μm.

10. The composite dielectric structure of claim 1, wherein the first dielectric ceramic material and / or the second dielectric ceramic material comprises a mixture of the glass material or the glass-based material and ceramic powder; the volume percentage of the glass material or the glass-based material in the interleaved layers is higher than the volume percentage of the glass material or the glass-based material in the mixture of the first dielectric ceramic material, and higher than the volume percentage of the glass material or the glass-based material in the mixture of the second dielectric ceramic material.

11. The composite dielectric structure of claim 10, wherein the volume percentage of the glass material or the glass-based material in the first dielectric ceramic layer is 13%-33%, and the volume percentage of the glass material or the glass-based material in the second dielectric ceramic layer is 53%-63%.

12. The composite dielectric structure of claim 10, wherein in the mixture of the first dielectric ceramic material and / or the second dielectric ceramic material, the glass material or the glass-based material is formed on at least a portion of the surface of the ceramic powder; the ceramic powders of the first dielectric ceramic material and the second dielectric ceramic material are different; and the staggered layer is in direct contact with the first dielectric ceramic layer and the second dielectric ceramic layer. 13 . The composite dielectric structure of claim 1 , wherein the first dielectric ceramic layer is disposed in a filter element, and the second dielectric ceramic layer is disposed in an antenna element. 14 . The composite dielectric structure as claimed in claim 1 , wherein the first dielectric ceramic layer, the second dielectric ceramic layer and the staggered layer are stacked along a stacking direction, and a thickness of the first dielectric ceramic layer is different from a thickness of the second dielectric ceramic layer in the stacking direction.

15. A method for manufacturing a composite dielectric structure using a mixed ceramic material, comprising the following steps: Providing a green embryo of at least one first dielectric ceramic layer, wherein the green embryo comprises a first dielectric ceramic material and has a first dielectric constant; Providing at least one green embryo of a second dielectric ceramic layer, wherein the green embryo comprises a second dielectric ceramic material and has a second dielectric constant; Providing at least one staggered layer of green embryos; Stacking the green sheets of the interleaved layer between the green sheets of the first dielectric ceramic layer and the green sheets of the second dielectric ceramic layer to form a multilayer structure, wherein the interleaved layer comprises a glass material or a glass-based material powder, the weight percentage of which is at least 90%-100% of the total material of the green sheets of the interleaved layer; and A low temperature co-firing process is performed on the multi-layer structure to form a composite dielectric structure.

16. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15, wherein the green body of at least the first or second dielectric ceramic layer is formed by mixing ceramic powder, solvent and binder, and wherein the third thickness of the staggered layer is less than a first thickness of the first dielectric ceramic layer and less than a second thickness of the second dielectric ceramic layer. 17 . The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15 , wherein the first dielectric constant is greater than the second dielectric constant.

18. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15, wherein the first dielectric constant is greater than four times the second dielectric constant.

19. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15, wherein the staggered layer comprises a high temperature liquid phase material having a softening point lower than the softening point of the first dielectric ceramic material and the softening point of the second dielectric ceramic material.

20. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15, wherein the softening point of the high temperature liquid phase material is 400-600°C.

21. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15, wherein the glass material or the glass-based material powder is selected from the group consisting of alkali oxides, inorganic glass mixtures and combinations thereof.

22. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 21, wherein the inorganic glass mixture comprises a mixture of phosphate glass, silicon oxide, aluminum oxide, potassium oxide, sodium oxide and boron oxide; the thickness of at least the green body of the interleaved layer is between 40 μm and 50 μm; the softening point of the glass material or the glass-based material powder of at least the green body of the interleaved layer is between 500° C. and 600° C., and is at least 100° C. lower than the softening points of the first dielectric ceramic layer and the second dielectric ceramic layer, respectively.

23. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15, wherein at least the material of the interlaced layers of green body further comprises a binder and a solvent, and the weight percentages of the glass material or the glass-based material powder, the binder and the solvent are 40-60%, 6-15% and 40-60% respectively.

24. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15, wherein the first dielectric ceramic material and / or the second dielectric ceramic material comprises a mixture of glass material or glass-based material powder and ceramic powder; the weight percentage of the glass material or glass-based material powder in the interlaced layer green body is higher than the weight percentage of the glass material or glass-based material powder in the first dielectric ceramic material mixture, and higher than the weight percentage of the glass material or glass-based material powder in the second dielectric ceramic material mixture.

25. The method for manufacturing a composite dielectric structure using a mixed ceramic material as claimed in claim 15, wherein the material of at least one embryo in the staggered layer comprises 93%-100% by volume of a glass material or a glass-based material powder and 5%-7% by volume of a ceramic powder; the first dielectric ceramic material and / or the second dielectric ceramic material comprises a mixture of a glass material or a glass-based material powder and a ceramic powder; the weight percentage of the glass material or the glass-based material powder in the material of at least the embryo in the staggered layer is 90%-100%; the weight percentage of the glass material or the glass-based material powder in the material of at least one embryo of the first dielectric ceramic layer is 10%-30%; the weight percentage of the glass material or the glass-based material powder in the material of at least the embryo of the second dielectric ceramic is 50%-60%.

26. The method for manufacturing a composite dielectric structure using a mixed ceramic material as described in claim 15, wherein at least one embryonic form of the first dielectric ceramic layer and at least one embryonic form of the second dielectric ceramic layer are stacked with at least one embryonic form of the interleaved layer along a stacking direction, and a first thickness of the embryonic form of the first dielectric ceramic layer and a second thickness of the embryonic form of the second dielectric ceramic layer are different in the stacking direction.